Non‐classical Non‐covalent σ‐Hole Interactions in Protein Structure and Function: Concepts for Potential Protein Engineering Applications. Issue 7 (24th February 2023) - Walker, Margaret G.; Mendez, C. Gustavo; Ho, P. Shing
Abstract: The structures and associated functions of biological molecules are driven by noncovalent interactions, which have classically been dominated by the hydrogen bond (H‐bond). Introduction of the σ‐hole concept to describe the anisotropic distribution of electrostatic potential of covalently bonded elements from across the periodic table has opened a broad range of nonclassical noncovalent ( nc NC) interactions for applications in chemistry and biochemistry. Here, we review how halogen bonds, chalcogen bonds and tetrel bonds, as they are found naturally or introduced synthetically, affect the structures, assemblies, and potential functions of peptides and proteins. This review intentionally focuses on examples that introduce or support principles of stability, assembly and catalysis that can potentially guide the design of new functional proteins. These three types of nc NC interactions have energies that are comparable to the H‐bond and, therefore, are now significant concepts in molecular recognition and design. However, the recently described H‐bond enhanced X‐bond shows how synergism among nc NC interactions can be exploited as potential means to broaden the range of their applications to affect protein structures and functions. Abstract : The nonclassical noncovalent interactions (halogen bonding, chalcogen bonding and tetrel bonding) are reviewed in the context of their contributions to the structure and associated functions of peptides and proteins.